Optimization of a non-arsenic iron-based superconductor for wire fabrication. (13th March 2015) - Mitchell, Jonathan E; Hillesheim, Daniel A; Bridges, Craig A; Paranthaman, M Parans; Gofryk, Kris; Rindfleisch, Matt; Tomsic, Mike; Sefat, Athena S
Abstract: We report on the optimization of synthesis of iron selenide-based superconducting powders and the fabrication of selenide-based wire. The powders were synthesized by an ammonothermal method, whereby Ba is intercalated between FeSe layers to produce Ba x (NH3 ) y Fe2 Se2, with tetragonal structure similar to A Fe2 X 2 ( X : As, Se), '122', superconductors. The optimal T c (up to 38 K) and Meissner and shielding superconducting fractions are obtained from the shortest reaction time ( t ) of reactants in liquid ammonia (30 min). With the increase of t, a second crystalline 122 phase, with a smaller unit cell, emerges. A small amount of NH3 is released from the structure above ∼200 °C, which results in loss of superconductivity. However, in the confined space of niobium/Monel tubing, results indicate there is enough pressure for some of NH3 to remain in the crystal lattice, and thermal annealing can be performed at temperatures of up to 780 °C, increasing wire density and yielded a reasonable T c ≈ 16 K. Here, we report of the first successful wire fabrication of non-arsenic high- T c iron-based superconductor. Although bulk materials are estimated to carry critical current densities >100 kA cm −2 (4 K, self-field), the current transport within wires need to be optimized ( J c ∼ 1 kA cm −2 ).